2014
DOI: 10.1590/1981-8637201400040000022648
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength to dentin of total-etch and self-etch adhesive systems

Abstract: Objective To assess the bond strength to dentin of the Single Bond (3M ESPE) and XP Bond (Dentsply) total-etch and Adper SE Plus (3M ESPE) self-etch adhesive systems. MethodsFifteen healthy human third molars were randomly allocated across three different groups of five teeth each according to the adhesive system. The occlusal portion of each tooth was removed under refrigeration using a flexible diamond disc (EXTEC, Enfield, CT, USA) down to an area of dentin that did not reveal enamel, as confirmed under a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…In the present study, the association of Adper Single bond (3M Espe) with the Beautifil flow plus and Beautifil II (Shofu) is the most beneficial, the study shows that there is no marginal microleakage. The result is consistent with Santos et al which in their study showed that the ER adhesive system presented the best resistance to dentin, concluding that these adhesive systems are superior to SE adhesives [15].…”
Section: Resultssupporting
confidence: 91%
“…In the present study, the association of Adper Single bond (3M Espe) with the Beautifil flow plus and Beautifil II (Shofu) is the most beneficial, the study shows that there is no marginal microleakage. The result is consistent with Santos et al which in their study showed that the ER adhesive system presented the best resistance to dentin, concluding that these adhesive systems are superior to SE adhesives [15].…”
Section: Resultssupporting
confidence: 91%
“…Our study reports showed the total-etch bonding system had a higher µSBS strength compared to one-step self-etch adhesives. This is supported the results of earlier researchers, such as Torres et al [18] and Dos Santos, R.A et al [19]. Solvent properties, like vaporization speed, drying patterns, and penetration properties, have been reported to influence the bond strength.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 50 single-rooted freshly extracted specimens were cleaned and stored in saline solution till evaluated. 2 Polishing of teeth was done using the standard protocol by pumice slurry and water. And the teeth were sectioned coronally and embedded in acrylic resin in a cylindrical mold of metal with dimensions 2 × 2 breadth ( Fig.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%